Efektivitas Model Pembelajaran Kooperatif Tipe Think-Talk-Write (TTW) terhadap Hasil Belajar Siswa pada Materi Sistem Reproduksi Kelas IX di SMPN 11 Gresik - Aini, Vera Nur (Indonesian Journal of Science Learning (IJSL), 2022)
This research was conducted because of the low learning outcomes of class IX students of SMPN 11 Gresik. This is because the learning model applied is a conventional model that only focuses on lectures, especially reproductive system material so it becomes one of the factors causing the low science learning outcomes for students. Therefore, researchers want to make improvements to the learning process by using the Think-Talk-Write (TTW) cooperative learning model which is expected to be a solution to these problems. The focus of this study was to determine the effectiveness of the Think-Talk-Write (TTW) cooperative learning model in learning science, especially reproductive system material in class IX students of SMPN 11 Gresik. This study aims to determine the effectiveness of the Think-Talk-Write (TTW) cooperative learning model in the science learning process on the reproductive system material in class IX students of SMPN 11 Gresik. This research is a quantitative study using a quasi-experimental research type with a pretest-posttest control group design. Data collection techniques in this study through tests, interviews, questionnaires, and documentation. Data analysis using independent sample t-test. The results showed that there was a significant difference between the experimental class and the control class as evidenced by the results of the independent sample t-test showing a significant value that was smaller than the alpha value, namely 0.001 <0.05. From the results of the study, it can be concluded that the Think-Talk-Write (TTW) cooperative learning model is effectively applied in science learning on reproductive system material in class IX students of SMPN 11 Gresik.